The Determinants of Underpricing for Seasoned Equity Offers - Corwin, Shane A. (Journal of Finance, 2003)
Abstract Seasoned offers were underpriced by an average of 2.2 percent during the 1980s and 1990s, with the discount increasing substantially over time. The increase appears to be related to Rule 10b‐21 and to economic changes affecting both IPOs and SEOs. Consistent with temporary price pressure, underpricing is positively related to offer size especially for securities with relatively inelastic demand. Underpricing is also positively related to price uncertainty and, after Rule 10b‐21, to the magnitude of preoffer returns. Additionally, I find that underpricing is significantly related to underwriter pricing conventions such as price rounding and pricing relative to the bid quote.